Optimization of APS Process Parameters Using a Designof Experiment for CSZ ( CeO2 Stabilized Zirconia) Coatings - Altuncu, Ekrem; Uste, Fatih (International Conference on Plasma Surface Engineering, 2013)
Air Plasma Sprayed (APS) Ceria Stabilized Zirconia (CSZ) coatings have been extensively used as alternative material yo Yttria Stabilized Zirconia (YSZ) in the gas turbine industries due to the good mechanical properties and hot corrosion resistance at an elavated temperatures. Due to the high velocity and temperature gradients in the plasma jet, any changes in the process parameters can result in significant changes in the particle properties and consequently in the microstructure of the coating. For increasing coating quality, operational primer process parameters as plasma gas flow rates, plasma current, spray distance must be optimized. The statistically designed taguchi experiments and regression analysis are used to determine the effects of processing parameters on mechanical and microstructural properties of coatings. The effect of changing the processing parameters on properties such as density, thickness, deposition efficiency and the amount of porosity in the coatings has been investigated in this study. Results showed that the CSZ has a higher deposition efficiency and denser microstructure than the YSZ systems.